Live-food enriched with Chlorella vulgaris as a potential supplemental diet to enhance performance and immune response of Tor tambroides larvae (Bleeker 1854) - Joshua, Wizilla Janti; Zulperi, Zarirah; Kamarudin, Mohd Salleh; Ikhsan, Natrah; Chin, Yong Kit; Ina-Salwany, Md Yasin; Yusoff, Fatimah Md (Elsevier, 2024)
Tor tambroides is one of the Tor species identified in Southeast Asia with a promising aquaculture potential in Malaysia, fetching market price of up to USD 53 per kilogram. It is a slow grower that takes more than two years to reach marketable body weight (∼800 g) in captivity. This study was designed to establish the C. vulgaris enriched Artemia sp. and Moina sp. in enhancing the growth performance of T. tambroides larvae. The larvae were divided into five treatments, control (C) (commercial feed); unenriched Moina (UM); enriched Moina (EM); unenriched Artemia (UA); enriched Artemia (EA). The concentration of C. vulgaris used during enrichment was 1 × 107 algal cells/mL. On 14 to 29 days after hatching (DAH), the larvae were co-fed with the commercial feeds and each treatment four times daily. The highest body weight gained were observed in the larval group fed with EA (18.56 ± 1.02 mg), followed by UA (15.89 ± 2.08 mg) and were statistically different as compared to the UM (6.89 ± 0.51) and EM (6.11 ± 1.09) and C (3.56 ± 1.20) (p < 0.05). The final total length was also the highest in larvae fed with EA (17.8 ± 0.04 mm), followed by UA (17.2 ± 0.0 mm), EM (16.4 ± 0.02 mm), UM (16.0 ± 0.02 mm) and the lowest in C (15.4 ± 0.02 mm). The larvae fed with EA also displayed a significant increase in specific growth rate (4.66), followed by UA (4.13) and were statistically different to UM (2.10), EM (1.88) and C (1.14) (p < 0.05). The relative growth rate of the larvae was the highest in EA (92.27) and lowest in C (17.68) (p < 0.05). The survival rate of the larvae was the highest in UM and EM with 89.4, followed by EA (89.13), UA (88.51) and C (84.7). The EA had high and positive upregulation of growth hormone genes (0.16 ± 0.13), myostatin gene (0.11 ± 0.10), MHCC1a gene (0.48 ± 0.12) and CC3 gene (0.28 ± 0.14) and were statistically different as compared to the control group. The enriched Artemia had enhancing effect on the growth performance and expression of the immune and growth genes of the larvae, potentially due to its nutritional contents and better ingestion by the larvae. The study suggests C. vulgaris enriched Artemia can be used in the hatcheries to improve the growth and survival of T. tambroides larvae, shorten its rearing period and increases its yield. © 2023 Elsevier B.V.